Business Strategy of PT Metra-Net in Executing Digital Business Initiatives from Its Parent Company (PT Telekomunikasi Indonesia) - Adhiwena, Edwin; Maarif, M. Syamsul; Yuliati, Lilik Noor (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze internal and external factors influencing PT Metra-Net’s business, identify strategic alternatives to support its digital business development, formulate strategic priorities to increase sales and growth, and derive managerial implications to align Metranet’s vision and mission with its parent company, Telkom Indonesia. The research employed a qualitative approach conducted from October to December 2024. Data were collected through Focus Group Discussions (FGDs) and in-depth interviews with seven participants: four internal Metranet personnel, two from Telkom, and one Metranet product user. The analysis used the External Factor Evaluation (EFE), Internal Factor Evaluation (IFE), SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM). Findings revealed various internal strengths and weaknesses, along with external opportunities and threats shaping Metranet’s business development. Based on these insights, strategic alternatives were formulated using SWOT analysis and then prioritized using QSPM to determine the most suitable options for implementation. The recommended strategies are expected to strengthen Metranet’s competitive advantage in the digital industry and enhance its contribution to Telkom. As the first study focusing on Metranet’s business development strategy, this research enriches the literature on strategic management, especially in the context of digital transformation and subsidiaries of state-owned enterprises.